Corporate governance in family businesses from Latin America, Spain and Portugal: A review of the literature. Issue 3 (1st August 2016) - Cortés, Diógenes Lagos; Botero, Isabel C.
Abstract : Purpose: The purpose of this paper is to summarize what is known about corporate governance in family firms from Ibero-American countries based on published research. Methodology: The authors conducted a literature search to identify the articles that have been published about the corporate governance of family firms in Latin America, Spain, and Portugal between 1980 and 2014. The authors found 38 articles that provide the sample for this review. Findings: The results indicate that research on governance in Ibero-American family firms has focussed on understanding structures and processes related to the business and ownership systems. However, generalization of results across the region is difficult because of the lack of systematic approach of studies and the focus on a small number of countries. Research limitations/implications: There are at least two limitations of this work: the small sample of projects identified for the review and the lack of systematic approach to research. Both of these may be due to the importance given to publishing the university context in this part of the world. As the culture of knowledge changes, the authors expect that research in this area will grow. Originality/value: Although previous research indicates that cultural characteristics affect governance system choices and understanding of family firms, not many studies explore the importance of culture in governance choices of family firms. This paper provides a baseline of the understanding of governance in Ibero-American family firms, and identifies important area for future research. Abstract : Propósito: La meta de este proyecto era resumir lo que sabemos acerca del gobierno corporativo en empresas familiares en países iberoamericanos. Metodología: Se realizó una búsqueda en la literatura para identificar artículos que se hubiesen publicado en el área de gobierno corporativo sobre empresas familiares en Latinoamérica, Portugal y España entre 1980 y el 2014. Se encontraron 38 artículos que representan la muestra en este resumen de la literatura. Conclusiones: Los resultados de esta investigación sugieren que la investigación sobre gobierno corporativo en empresas familiares iberoamericanas se ha centrado en entender las estructuras y los procesos relacionados a los sistemas de la empresa y la propiedad. Sin embargo, la generalización de estos resultados a través de toda la región es difícil porque falta de investigaciones sistemáticas sobre temas similares y por la concentración de estudios en países específicos. Limitaciones: Este trabajo tiene por lo menos dos limitaciones: el tamaño de la muestra y la falta de estudios sistemáticos en investigaciones de esta área. Estas dos limitaciones pueden están relacionadas con la importancia que se le da a la publicación de investigaciones en esta región del mundo. A medida que la cultura del conocimiento en esta región cambie, se notara la proliferación de más estudios en el área de gobierno corporativo en empresas familiares iberoamericanas. Originalidad y Valor: A pesar que investigaciones previas indican que las características culturales afectan las decisiones sobre sistemas de gobierno corporativo y como entendemos las empresas familiares, no hay mucha investigación acerca de la importancia de la cultura en las decisiones de gobierno en empresas familiares. Este trabajo representa una base para entender el gobierno corporativo en empresas familiares iberoamericanas y para identificar áreas de énfasis en investigaciones futuras.